Feeding whole-plant ensiled corn stover affects growth performance, blood parameters, and Cecal microbiota of Holdobagy goose - Wang, Xianze; Li, Guangquan; Wang, Huiying; Liu, Yi; Yang, Yunzhou; Wang, Cui; Gong, Shaoming; He, Daqian (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the effects of adding Whole-plant ensiled corn stalks (WECS) to the diet of Holdorbagy geese on their growth performance, serum parameters, and cecal microbiota. One hundred and forty-four 6-week-old Holdorbagy geese were randomly assigned to one of three groups: a control group (0% WECS), a group fed 15% WECS and 85% concentrated feed(15% WECS), and a group fed 30% WECS and 70% concentrated feed (30% WECS). The results showed that the F/G ratio of the 15% WECS group was significantly higher than that of the 0% WECS group (p<0.05), and the ADFI of both the 15% and 30% WECS groups was significantly higher than that of the 0% WECS group (p<0.05). The LDH level of the 30% WECS group was significantly lower than that of the 0% WECS group (p<0.05), and as the level of WECS supplementation increased, there was a tendency for Fe levels to increase and Zn levels to decrease (p>0.05). The observed_species, Shannon, and Pielou_e indices of the 30% WECS group were significantly higher than those of the 0% and 15% WECS groups (p<0.05), while the Simpson index of the 15% WECS group was significantly lower than that of the 0% WECS group (p<0.05). Spearman's analysis showed that the abundance of Faecalibacterium was negatively correlated with ADFI (p<0.05), while Faecalibacterium, Alistipes, Rikenella, and Butyricimonas were negatively correlated with the F/G ratio (p<0.05). Faecalibacterium and Rikenella were negatively correlated with Fe levels in the serum (p<0.05), while Desulfovibrio and Rikenella were negatively correlated with Zn levels in the serum (p<0.05), and Bilophila was positively correlated with Zn levels in the serum (p<0.05) and with LDH levels in the serum (p<0.05). Therefore, this study concluded that WECS can be a long-term stable feed source for geese and can help reduce feeding costs. However, adding WECS can affect the absorption of Zn by geese, and the amount of WECS added needs to be monitored, and Zn needs to be supplemented in the diet to meet the needs of geese. Adding 30% WECS can increase the richness, evenness, and diversity of the cecal microbiota.